(3eYGde GdYdeGA aj agQSJ cJH GdTjYI hCSeGA GdeUfajf efge bOjeG hMOjKGs - (3GdnqSQhj GdeGRfOQGfj, CHh LYaQ, QTjO GdOjf, eMeO Hf Ydj Hf TgQBThH, J (B588(3g`s ((3Ydj Hf bhGe GdOjf Hf eMeO GddjKjs)
(3ChdgG (B:s
(3GdMeO ddg (B.. (3hEf cGf bO LeY TjNfG CHh LYaQ GdWhSj aj Pdc eGdG fXjQ dg EdG Cf gPG GdeNJUQ ajg RhGFO ajchf EPG JJeI dg hbO ROJ ajg fMh SJeGFI eUfa hCTQJ Edi GdeMPha ef cJGHg (B...s
(3BNQgG (B:s
...(3hef GdeJcdajf fMh MSGf Hf KGHJ heQhGf Hf CHj MaUI hGHfg eMehO hGdCTLY hCHh HOjd GdJejej hEHQGgje Hf GdYHGS hefUhQ Gdabjg hGdeZQHj hPdc MRH YXje hGddg GdeTchQs
(3JHUQI GdYfhGf (B:s
(3JJeI eYGde GdOjf ddWhSjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\279s
(3GdPQjYI (B21\4606s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs